Direct regulation of aromatase B expression by 17β-estradiol and dopamine D1 receptor agonist in adult radial glial cells - Xing, Lei; Esau, Crystal; Trudeau, Vance L. (Frontiers in Neuroscience, 2016)
Aromatase cytochrome P450arom (cyp19) is the only enzyme that has the ability to convert androgens into estrogens. Estrogens, which are produced locally in the vertebrate brain play many fundamental roles in neuroendocrine functions, reproductive functions, socio-sexual behaviors and neurogenesis. Radial glial cells (RGCs) are neuronal progenitor cells that are abundant in fish brains and are the exclusive site of aromatase B expression and neuroestrogen synthesis. Using a novel in vitro RGC culture preparation we studied the regulation of aromatase B by 17β-estradiol (E2) and dopamine (DA). We have established that activation of the dopamine D1 receptor (D1R) by SKF 38393 up-regulates aromatase B gene expression most likely through the phosphorylation of cyclic AMP response element binding protein (CREB). This up-regulation can be enhanced by low concentration of E2 (100 nM) through increasing the expression of D1R and the level of p-CREB protein. However, a high concentration of E2 (1 μM) and D1R agonist together failed to up-regulate aromatase B, potentially due to attenuation of esr2b expression and p-CREB levels. Furthermore, we found the up-regulation of aromatase B by E2 and DA both requires the involvement of esr1 and esr2a. The combined effect of E2 and DA agonist indicates that aromatase B in the adult teleost brain is under tight control by both steroids and neurotransmitters to precisely regulate neuroestrogen levels.